Interference of distinct invariant chain regions with superantigen contact area and antigenic peptide binding groove of HLA-DR - Vogt, Anne B.; Stern, Lawrence J.; Amshoff, Christine; Dobberstein, Bernhard; Hämmerling, Günter J.; Kropshofer, Harald (The journal of immunology, 1995)
In the endoplasmic reticulum, MHC class II αβ dimers associate with the trimeric invariant chain (li), generating a nine-subunit (αβ li)3 complex. In the presence of li, the peptide binding groove is blocked, so that loading with self or antigenic peptides can only occur after proteolytic removal of li in specialized post-Golgi compartments. The class II-associated invariant chain peptide region of li (about residues 81-104) is known to mediate binding to class II molecules and blockade of the groove, but this does not exclude additional contact sites for li. Using a set of overlapping li peptides and recombinant soluble li, we demonstrate here that a large segment of li encompassing approximately residues 71 to 128 interacts with HLA-DR molecules. The N- and C-terminal regions of this li segment appear to bind outside the peptide groove to the contact area for the staphylococcal superantigen Staphylococcus aureus enterotoxin B on the α 1 domain. The core region of this segment (residues 95-108) prevents binding of antigenic peptides, probably by interaction with the peptide groove. Occupation of the groove with antigenic peptides abolishes binding not only of the core region, but also that of those li peptides that bind outside the groove. These findings suggest the existence of distinct conformational states of class II molecules, with li binding preferentially to one form.